A new step-wise surgical technique of knapsack-like uterine compression sutures for intractable postpartum hemorrhage in cesarean section - Lei Han; Baolin Zhang; Huishu Xu; Hongmei Yin; Yiwei Pang; Xianghui Zhang; Qingliang Zhai; Xiaofeng Liu; Yanlin Wang; Caiying Zhang; Yingjiang Xu; Yanni Liu; et al. (BMC, 2024)
Abstract Background Intractable postpartum hemorrhage (PPH) during cesarean section has been a significant concern for obstetricians. We aimed to explore the effectiveness and safety of a new type of uterine compression suture, the step-wise surgical technique of knapsack-like sutures for treating intractable PPH caused by uterine atony and placenta factors in cesarean section. Methods The step-wise surgical technique of knapsack-like sutures was established on the basis of the artful combination of vertical strap-like sutures and an annular suture-ligation technique. This novel surgical technique was applied to 34 patients diagnosed with PPH during cesarean section due to severe uterine atony and placental factors in our department. The hemostatic effects, clinical outcomes and follow-up visit results were all reviewed and analyzed. Results This new uterine compression suture successfully stopped bleeding in 33 patients, and the effective rate was 97.06%. Only 1 patient failed and was changed to use bilateral uterine arterial embolization and internal iliac artery embolization. The follow-up visits indicated that 33 patients restored menstruation except for 1 who was diagnosed with amenorrhea. The gynecological ultrasound tests of all the patients suggested good uterine involutions, and they had no obvious complaints such as hypogastralgia. Conclusions This step-wise surgical technique of knapsack-like uterine compression sutures can compress the uterus completely. It is a technique that can conserve the uterus and fertility function without special equipment in caesarean section for PPH, with the characteristics of being safe, simple and stable (3 S) with rapid surgery, reliable hemostasis and resident doctor to operation (3R).